Corporate policy and the ethics of competitor intelligence gathering - Paine, Lynn Sharp (Journal of business ethics, 1991)
Competitor intelligence, information that helps managers understand their competitors, is highly valued in today's marketplace. Firms, large and small, are taking a more systematic approach to competitor intelligence collection. At the same time, information crimes and litigation over information disputes appear to be on the rise, and survey data show widespread approval of unethical and questionable intelligence-gathering methods. Despite these developments, few corporations address the ethics of intelligence gathering in their corporate codes of conduct. Neither managers nor management educators have paid sufficient attention to this topic. From a review of questionable intelligence-gathering practices reported in various literatures, the author identifies some important ethical principles to help managers draw the line between legitimate and illegitimate methods of information acquisition. The paper also discusses the costs of failure to heed these principles and suggests steps managers can take to provide ethical leadership in this area.